Metabolic Syndrome in Inversely Related to Cardiorespiratory Fitness in Male Career Firefighters - Baur, Dorothee M.; Kales, Stefanos N.; Christophi, Costas A. (My University, 2012)
Baur, DM, Christophi, CA, and Kales, SN. Metabolic syndrome is inversely related to cardiorespiratory fitness in male career firefighters. J Strength Cond Res 26(9): 2331-2337, 2012-Cardiovascular disease (CVD) accounts for 45% of on-duty fatalities among firefighters, occurring primarily in firefighters with excess CVD risk factors in patterns resembling the metabolic syndrome (MetSyn). Additionally, firefighters have a high prevalence of obesity and sedentary behavior suggesting that MetSyn is also common. Therefore, we assessed the prevalence of MetSyn in firefighters and its association with cardiorespiratory fitness (CRF) in a cross-sectional study of 957 male career firefighters. The CRF was measured by maximal exercise tolerance testing (standard metabolic equivalent [METS]). The MetSyn was defined according to modified criteria from the Joint Scientific Statement. Group differences were compared using chi(2)-test and logistic regression. The prevalence of MetSyn was 28.3%. Firefighters in the lowest fitness category (METS <= 10) had a nearly 10-fold higher prevalence of MetSyn (51.2%) compared with colleagues in the highest fitness category (METS > 14) (MetSyn prevalence 5.2%) (p value < 0.0001, adjusted for age). In multivariate regression models, every 1-unit increase in METS decreased the odds of having the MetSyn by 31% (odds ratio 0.69 [95% confidence interval 0.63-0.76] [age adjusted]), whereas age had no significant effect after adjusting for CRF. We found a high prevalence of the MetSyn in this group of career emergency responders expected to be more active, fit, and relatively younger than the general population. Moreover, there is a highly significant inverse, dose-response association with CRF. Firefighters should be given strong incentives to improve their fitness, which would decrease prevalent MetSyn, a likely precursor of on-duty CVD events and contributor to CVD burden in this population.
Keywords: coronary-heart-disease; body-mass index; cardiovascular-disease; physical-activity; police officers; risk-factors